2021
DOI: 10.3390/nu13062067
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mediterranean Diet on Cognitive Functions in the Elderly Population

Abstract: At present, due to the demographic changes and the rise of senior population worldwide, there is effort to prolong an active life of these people by both pharmacological and non-pharmacological strategies. The purpose of this article is, on the basis of the literature review of recent clinical studies, to discuss one of such strategy, i.e., the effect of Mediterranean Diet (MedDiet) on the cognitive functions among both the cognitively unimpaired and impaired elderly people. The methodology includes a literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 55 publications
0
12
0
1
Order By: Relevance
“…The most important positive effects include reduced all-cause mortality [6,8,9], primary prevention of cardiovascular disease [10], lower cancer incidence and mortality [6,11], reduced risk for development of type II diabetes [12][13][14], obesity and metabolic syndrome [13]. Benefits of MD also include safeguarding of mental health, such as better cognitive performance with higher adherence to the MD [15], reduced risk of depression and cognitive impairment [16], lesser mental distress [17], and overall better health-related quality of life [18,19]. Moreover, MD was even shown to be an efficient treatment strategy for major depressive episodes [20].…”
Section: Introductionmentioning
confidence: 99%
“…The most important positive effects include reduced all-cause mortality [6,8,9], primary prevention of cardiovascular disease [10], lower cancer incidence and mortality [6,11], reduced risk for development of type II diabetes [12][13][14], obesity and metabolic syndrome [13]. Benefits of MD also include safeguarding of mental health, such as better cognitive performance with higher adherence to the MD [15], reduced risk of depression and cognitive impairment [16], lesser mental distress [17], and overall better health-related quality of life [18,19]. Moreover, MD was even shown to be an efficient treatment strategy for major depressive episodes [20].…”
Section: Introductionmentioning
confidence: 99%
“…The age difference may more favorably reflect the relationship between the MedDiet and cognitive performance, as the MedDiet may have a greater impact on cognitive health later rather than earlier in life. In general, the use of different outcome measures, varied research samples, and measured target domains may affect the result of the association between the MedDiet and cognitive performance [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The MD is globally one of the most studied dietary patterns due to its major health benefits [10]. Studies have shown that higher adherence to the MD is associated with a reduced risk of developing cardiovascular diseases, diabetes, obesity, cognitive diseases and depression [11][12][13][14][15]. Recent findings showed evidence that the MD has a lipid-lowering effect, protects against oxidative stress, inflammation and platelet aggregation, regulates signals involved in the pathogenesis of cancer, inhibits nutrient sensing pathways by specific amino acid restriction and influences metabolic health through gut microbiota [16,17].…”
Section: Introductionmentioning
confidence: 99%